2020
DOI: 10.1101/2020.08.24.264192
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pathogenicity, immunogenicity, and protective ability of an attenuated SARS-CoV-2 variant with a deletion at the S1/S2 junction of the spike protein

Abstract: SARS-CoV-2 contains a PRRA polybasic cleavage motif considered critical for efficient infection and transmission in humans. We previously reported that virus variants with spike protein S1/S2 junction deletions spanning this motif are attenuated. Here we characterize a further cell-adapted SARS-CoV-2 variant, Ca-DelMut. Ca-DelMut replicates more efficiently than wild type or parental virus in cells, but causes no apparent disease in hamsters, despite replicating in respiratory tissues. Unlike wild type virus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
(52 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, the original 2003 SARS-CoV lacked a furin CS and was clearly transmitted between people, although this usually occurred during a symptomatic phase rather than asymptomatically or pre-symptomatically, thus allowing the virus outbreak to be controlled by public health measures (Liu, Gayle, Wilder-Smith, & Rocklov, 2020). Several recent studies have investigated the pathogenicity of naturally occurring or engineered deletion mutants in the hamster model, and shown that viruses lacking the furin CS are attenuated for replication and pathogenicity (Johnson et al, 2020; Lau et al, 2020; Wang et al, 2020; Wong et al, 2020). We, like others, did not find that SARS-CoV-2 induced significant clinical signs in ferrets, so were unable to assess the effect of the CS mutation on viral pathogenesis here.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the original 2003 SARS-CoV lacked a furin CS and was clearly transmitted between people, although this usually occurred during a symptomatic phase rather than asymptomatically or pre-symptomatically, thus allowing the virus outbreak to be controlled by public health measures (Liu, Gayle, Wilder-Smith, & Rocklov, 2020). Several recent studies have investigated the pathogenicity of naturally occurring or engineered deletion mutants in the hamster model, and shown that viruses lacking the furin CS are attenuated for replication and pathogenicity (Johnson et al, 2020; Lau et al, 2020; Wang et al, 2020; Wong et al, 2020). We, like others, did not find that SARS-CoV-2 induced significant clinical signs in ferrets, so were unable to assess the effect of the CS mutation on viral pathogenesis here.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the deletion of QTQTN (mut-del2) diminished SARS-CoV-2 entry and infection in Vero-E6 cells (40). Furthermore, three FCS-related deletion mutants, ΔPRRA↓, ΔRAR↓SVAS, and ΔNSPRRAR↓SVA, have been shown to have reduced replication in vitro and lung disease in animal models (44,49,50), strongly supporting that the FCS is a virulencerelated motif. Since the ΔQTQTN also abolished the furin cleavage (40), we speculate mut-del2 mutant should have reduced lung disease in animals as well.…”
Section: Discussionmentioning
confidence: 88%
“…Importantly, the deletion of QTQTN (mut-del2) diminished SARS-CoV-2 entry and infection in Vero-E6 cells (41). Furthermore, three FCS-related deletion mutants, DPRRA;, DRAR;SVAS, and DNSPRRAR;SVA, have been shown to have reduced replication in vitro and lung disease in animal models (44,52,53), strongly supporting that the FCS is a virulence-related motif. Since the DQTQTN also abolished furin cleavage (41), we speculate that the mut-del2 mutant should have reduced lung disease in animals as well.…”
Section: Discussionmentioning
confidence: 89%